Drought Resilience through Livelihood Diversification among Somali Pastoralists: A Case Study of Yocale Woreda - Kader Ahmed Abdulahi (Journal of Arts, Humanities and Social Science)
Pastoralist communities in the Somali region, especially in the Yocale district, face significant challenges because to frequent droughts and changing environmental conditions. The strategies these communities use to diversify their sources of income are examined in this study. Data was collected using a mixed research approach and a cross-sectional survey design from 204 randomly selected families in four kebeles in the Yocale area. According to the findings, pastoralists employ a variety of coping strategies before, during, and after droughts, including moving, diversifying their herds, selling cattle, putting down weak animals, consuming wild fruit, selling charcoal, depending on social support, and changing up their revenue streams. One important strategy was herd diversification, with an emphasis on drought-tolerant species like goats and camels. In the early phases of a drought, selling livestock helps raise money for necessities. However, the report points out that adopting livelihood diversification presents some difficulties, including limited credit availability, insufficient capital, poor infrastructure, and a lack of skills. The results highlight the necessity of programs and policies that assist pastoralists' customary adaptive strategies while removing obstacles to diversification.